2008
DOI: 10.1089/cpb.2007.0080
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Computing Skills of Low-Achieving Students via E-Learning: A Design Experiment of Web-Based, Problem-Based Learning and Self-Regulated Learning

Abstract: A design experiment was conducted applying Web-based problem-based learning (PBL), self-regulated learning (SRL), or their combination to help low-achieving students improve their skills of deploying application software in a compulsory course at a vocational school in Taiwan. The effects were encouraging and mostly positive. However, students' inertia to change routines of learning inherited from a culture of taking standard tests found in e-learning practice is quite common. A teacher's awareness of these ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…31,32 Studies examining how students learn complex and challenging tasks have suggested that successful students deploy key self-regulatory strategies and processes. 29,33 In this regard, the intervention of Web-mediated SRL may improve both Case 1 and Case 2 students' learning and led to the nonsignificant difference.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…31,32 Studies examining how students learn complex and challenging tasks have suggested that successful students deploy key self-regulatory strategies and processes. 29,33 In this regard, the intervention of Web-mediated SRL may improve both Case 1 and Case 2 students' learning and led to the nonsignificant difference.…”
Section: Discussionmentioning
confidence: 94%
“…As has been found in previous research on the effects of Web-mediated SRL, students who received this intervention of SRL may have better learning performance. 25,[29][30][31] It is also indicated that self-regulation helped students become more responsible for their learning and contributed to further success. 31,32 Studies examining how students learn complex and challenging tasks have suggested that successful students deploy key self-regulatory strategies and processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…50, No. 2, 121-132, http://dx.doi.org/10.1080/14703297.2012 Ó 2013 Taylor & Francis enrolling students with lower levels of academic achievement (Lee, Shen, & Tsai, 2008a). Students identified as low-academic achievers are one or more grade-levels behind their peers in basic reading, language, or mathematical skills (Reglin, 1993;Slavin, 1991), with some learning difficulties (Zohar & Dori, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a continuing debate about the effective design of online learning environments (Azevedo, 2005). It has been suggested that vocational students in Taiwan are more addicted to the Internet than those students in the more academic universities (Lee et al, 2008a;Yang & Tung, 2007). For example, they may spend much time on browsing shopping websites, playing online games or interacting through Facebook.…”
Section: Introductionmentioning
confidence: 99%